2019
DOI: 10.1183/13993003.00986-2018
|View full text |Cite
|
Sign up to set email alerts
|

Predicting EGFR mutation status in lung adenocarcinoma on computed tomography image using deep learning

Abstract: Epidermal growth factor receptor (EGFR) genotyping is critical for treatment guidelines such as the use of tyrosine kinase inhibitors in lung adenocarcinoma. Conventional identification of EGFR genotype requires biopsy and sequence testing which is invasive and may suffer from the difficulty of accessing tissue samples. Here, we propose a deep learning model to predict EGFR mutation status in lung adenocarcinoma using non-invasive computed tomography (CT).We retrospectively collected data from 844 lung adenoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
305
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 342 publications
(317 citation statements)
references
References 39 publications
8
305
2
2
Order By: Relevance
“…Radiomics, which involves extracting quantitative features from medical images, is capable of generating imaging biomarkers as decision support tools for clinical practice [18][19][20][21][22][23][24][25][26]. The traditional radiomics method utilizes single-phase medical images for evaluation or prediction, which neglects the tumor change during treatment or following up.…”
Section: Introductionmentioning
confidence: 99%
“…Radiomics, which involves extracting quantitative features from medical images, is capable of generating imaging biomarkers as decision support tools for clinical practice [18][19][20][21][22][23][24][25][26]. The traditional radiomics method utilizes single-phase medical images for evaluation or prediction, which neglects the tumor change during treatment or following up.…”
Section: Introductionmentioning
confidence: 99%
“…into mineable data (16,17), which has been widely applied in the prediction of preoperative distant metastasis, histologic subtype classification, and so on (18)(19)(20). Prognosis based on radiomics is gaining popularity as associations between radiomic features and the underlying genomic patterns emerge in various cancers (21)(22)(23)(24). On one hand, a latest study showed that a subset of radiomic features were able to consistently capture texture information about the underlying tissue histology, but some of them were incapable to be observed at the purely human level (25,26).…”
Section: Introductionmentioning
confidence: 99%
“…The most recent review and meta-analysis of CT and clinical characteristics to predict the risk of EGFR mutation confirms that CT features with the highest correlation with EGFR mutation are from the nodule and other structures of the lung 30 . Also, another work based on deep learning techniques with an interpretable visual output, identified that the regions surrounding the nodule were the most relevant for the classification decision 18,31 . In our opinion, it is crucial to emphasise this characteristic, as it might change the direction and broaden the analysis spectrum of future radiogenomics studies, which until now have been mainly focusing on the nodule or in a region of interest (ROI) around it [32][33][34] .…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…Studies in lung cancer have presented the association between EGFR mutation status and quantitative features extracted from computed tomography (CT) scans [14][15][16][17] . The most recent methods are based on convolutional neural networks, which are end-to-end approaches that allow to automatically learn the whole process, reducing the subjectivity and human effort 14,18 . Also, regarding qualitative features, recent works have shown that semantic human annotations of CT scans can be used to train a model to accurately predict EGFR mutation status, although the same was not verifiable for KRAS 19,20 .…”
Section: Introductionmentioning
confidence: 99%